Infectious bursal disease virus replication is inhibited by avain T cell chemoattractant chemokine CCL19 - Wang, Qiuxia; Chu, Fuming; Zhang, Xin; Hu, Huilong; Lu, Lang; Wang, Fang; Yu, Yan; Zhang, Yanhong; Ma, Jinyou; Xu, Zhiyong; Eldemery, Fatma; Ou, Changbo; et al. (Frontiers in Microbiology, 2022)
Chemokine CCL19 together with its receptor CCR7 is one of the most important factors recruiting immune cells into target organ during virus infection. Our previous study has shown that CCL19 played a vital role in the process of T cell trafficking into bursae during infectious bursal disease virus (IBDV) infection. In the current study, we hypothesized that CCL19 could exert direct influences on IBDV replication other than recruiting immune cells. A eukaryotic expression vector of pEGFP-N1/CCL19 was successfully constructed and identified by PCR, double enzymes digestion and sequencing. Different concentrations of pEGFP-N1/CCL19 plasmids were transfected into DF1 cells and CCL19 protein was highly expressed. Then, DF1 cells were infected with IBDV B87 strain post-transfection. Based on PCR and Western blot results, CCL19 could obviously decrease the gene levels of VP1 and VP2 and the protein levels of VP2 and VP3. When CCL19 was knocked down, the gene levels of VP1 and VP2 were significantly up-regulated. Moreover, indirect immunostaining revealed that the IBDV content was largely decreased after CCL19 over-expression. Additionally, CCL19 inhibitory effects might rely on activation of the JNK signal pathway. Taken together, chemokine CCL19 directly block IBDV replication in DF1 cells, indicating that CCL19 could play other crucial functions other than recruiting T cells during the pathogenesis of IBDV.